PENERAPAN MANAJEMEN RISIKO UNTUK MENINGKATKAN DAYA SAING DAN KEBERLANJUTAN USAHA PADA UMKM TERASA BOOSTER - Nurpratiwi, Tiara; Meilinda Anggreni; Twenty Mariza Syafitri; Dessy Carolina (Jurusan Akuntansi Politeknik Negeri Sriwijaya Palembang, 2025)
Micro, Small, and Medium Enterprises (MSMEs) often face structural vulnerabilities due to reactive management styles. This community service aims to transform the governance of MSME Terasa Booster, a breastfeeding supplement producer in Palembang, from a reactive to a proactive pattern through the application of risk management. The partner's problems include supplier dependency, stock damage risks due to infrastructure, and regulatory compliance. The implementation method was carried out strictly through preparation stages (FGD), education and training, tool development (working paper), and implementation mentoring. The results showed the successful identification of seven key risks mapped into priority zones. The main output, a customized